Influence of storage methods, refrigeration or freezing, on the toxicity of wastewater samples to oyster embryos. - LIBRALATO, Giovanni; AVEZZU', Francesco; VOLPI GHIRARDINI, Annamaria; LOSSO C (Environmental Technology, 2009)
One of the main concerns in wastewater whole effluent assessment is the sampling phase and the sample chain of custody before any toxicity evaluation. The major problem is related to establishing the correct method for sample storage in order to perform toxicity bioassays. The toxicity of some domestic and glass factory industrial wastewater samples stored both by refrigeration at 4 ± 1°C for no more than three days, and freezing at -18 ± 1°C for no more than one month was compared via the embryo larval development bioassay with the oyster Crassostrea gigas. The results showed no significant differences between the toxicities of refrigerated and frozen wastewater samples. The wastewater classification, according to a score based on four toxicity classes, showed that the preservation methods did not alter the toxicity classification of the samples. In particular, it was demonstrated that the samples considered as 'not acutely toxic' after refrigeration were also found to have this classification after freezing.